2014
DOI: 10.3141/2402-07
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Metering to Help Roundabouts Manage Peak Period Demands in the United States

Abstract: Roundabouts generally provide safety and other advantages. During peak hours, however, even moderate demands on an upstream approach can result in long delays and driver frustration over downstream movements. A metering signal is one way to ensure that all demands at a roundabout are adequately served. A roundabout metering signal regulates flow into the circle from one approach and thereby creates larger gaps in the circle for downstream entrants. Although metering signals have been used successfully around t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 1 publication
0
38
0
2
Order By: Relevance
“…They reported based on their case study that delay was reduced by 50% and number of conflict points by 34% compared to the existing configuration [11]. Hummer et al (2014) using a simple Highway Capacity Manual based macroscopic model evaluated where a meter might help to improve performance of a roundabout [12]. They found that signalized intersections generally produce lower delays than metered or unmetered roundabout in most of the tested cases.…”
Section: Troductionmentioning
confidence: 99%
“…They reported based on their case study that delay was reduced by 50% and number of conflict points by 34% compared to the existing configuration [11]. Hummer et al (2014) using a simple Highway Capacity Manual based macroscopic model evaluated where a meter might help to improve performance of a roundabout [12]. They found that signalized intersections generally produce lower delays than metered or unmetered roundabout in most of the tested cases.…”
Section: Troductionmentioning
confidence: 99%
“…Roundabouts generally provide better operational and safety characteristics over other typical intersections; see Flannery and Datta (1997); Flannery et al (1998); Al-Madani (2003); Sisiopiku and Oh (2001). However, the increase of traffic may become a concern for roundabouts due to their geometry and priority system -even with moderate demands, some roundabouts can still reach capacity; see Hummer et al (2014); Yang et al (2004). Moreover, traffic from minor-road approaches may experience significant delay if the circulating flow is heavy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, traffic from minor-road approaches may experience significant delay if the circulating flow is heavy. Previous research has focused mainly on enhancing roundabout mobility and safety with improved metering, or traffic signal controls, e.g., Hummer et al (2014); Yang et al (2004); Martin-Gasulla et al (2016); Xu et al (2016). These efforts investigate the potential of metering signals in improving roundabout operations during rush hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under unbalanced traffic flow conditions, roundabouts are likely to experience long queuing problems. [6][7][8] The other studies on unbalanced traffic conditions were conducted and the unbalanced flow was defined through the origin-destination factor. 9,10 In addition, the origin-destination factor may improve the estimation of roundabout capacity, in particular, with the unbalanced traffic conditions.…”
Section: Introductionmentioning
confidence: 99%